„Kwestia żydowska” w działalności ambasadora USA w Berlinie Williama E. Dodda (1933–1937) - Sołuba, Paulina (Acta Universitatis Lodziensis. Folia Historica, 2013)
William Edward Dodd was served as the United States ambassador in Germany from 1933 to 1937. New ambassador spoke the language fluently, he was also a graduate of the Leipzig University. In his four-and-one-half year mission to the Third Reich Dodds opinion about Germany evolved. Finally he became more and more convinced that Hitler and his associates were criminals. “Jewish question” played important role in Dodds turnaround. Before leaving to take up his post, Dodd consulted on the Jews situation in Germany. In Third Reich Dodd could his imagination confronted with reality. New ambassador observed how the Nazis systematically excluded Jews from participation in German life. Jews lost their jobs, their citizenship, and their civic rights. They were isolated and cut off from society. He tried to help persecuted people in immigration to United States. Ambassador attitude brought on tension in contact with the German government. This was the reason his recall. The German government told the State Department that Dodd could no longer function in Berlin. Ambassador resignation was announced in December 1937.